Correlación entre medidas lingüísticas: Algunas extensiones - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2023)
– In this paper we revisit the results that appeared originally in Coloma (2017) about the possible existence of negative correlation between linguistic measures, using a new database of 80 languages for which we have the same text (which is the fable known as "The North Wind and the Sun"). Most conclusions of the original paper become reinforced, especially the ones related to the existence of language complexity trade-offs. This is particularly clear when we look at partial correlation coefficients between three linguistic ratios (phonemes per syllable, syllables per word, and words per clause), especially when we use simultaneous-equation regression methods and instrumental variables.
Keywords: 330; efectos de compensación; correlación parcial; cocientes lingüísticos; ecuacionessimultáneas; variables instrumentales; complexity trade-off; partial correlation; linguistic ratios; simultaneous-equationregression; instrumental variables